Pendidikan Pendidikan Akhlak Dalam Al-Qur’an (QS. Al-Hujurat: 10-13 & QS. Al-Qalam: 4) - Khairunnida .; Mahyuddin Barni (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2025)
This study aims to explore the moral education values contained in Surah Al-Hujurāt verses 10–13 and Surah Al-Qalam verse 4, as well as their relevance to character formation in the modern era. The research focuses on essential principles of social ethics such as brotherhood, the prohibition of mockery, the avoidance of suspicion and backbiting, the affirmation of human equality, and the exemplary character of Prophet Muhammad ﷺ as the central model of moral education. This study employs a library research method by examining various tafsir books, academic journals, and scholarly works related to Islamic moral education. The findings indicate that these Qur’anic verses provide a comprehensive foundation for building noble character within educational settings, families, and society. Furthermore, they highlight the Qur’an’s role as a timeless source of moral guidance that remains highly relevant for shaping future generations with strong ethical values.